Deaths from violence in North Carolina, 2004: how deaths differ in females and males. (14th December 2006) - Sanford, C; Marshall, S W; Martin, S L; Coyne-Beasley, T; Waller, A E; Cook, P J; Norwood, T; Demissie, Z
Abstract : Objective: To identify gender differences in violent deaths in terms of incidence, circumstances, and methods of death. Design: Analysis of surveillance data. Setting: North Carolina, a state of 8.6 million residents on the eastern seaboard of the US. Subjects: 1674 North Carolina residents who died from violence in the state during 2004. Methods: Information on violent deaths was collected by the North Carolina Violent Death Reporting System using data from death certificates, medical examiner reports, and law enforcement agency incidence reports. Results: Suicide and homicide rates were lower for females than males. For suicides, females were more likely than males to have a diagnosis of depression (55% v 36%), a current mental health problem (66% v 42%), or a history of suicide attempts (25% v 13%). Firearms were the sole method of suicide in 65% of males and 42% of females. Poisonings were more common in female than male suicides (37% v 12%). Male and female homicide victims were most likely to die from a handgun or a sharp instrument. Fifty seven percent of female homicides involved intimate partner violence, compared with 13% of male homicides. Among female homicides involving intimate partner violence, 78% occurred in the woman's home. White females had a higher rate of suicide than African-American females, but African-American females had a higher rate of homicide than white females. Conclusions: The incidence, circumstances, and methods of fatal violence differ greatly between females and males. These differences should be taken into account in the development of violence prevention efforts.